The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/rs10040519
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Penetration Depth from Soil Effective Temperature in Microwave Radiometry

Abstract: Abstract:Soil moisture is an essential variable in Earth surface modeling. Two dedicated satellite missions, the Soil Moisture and Ocean Salinity (SMOS) and the Soil Moisture Active Passive (SMAP), are currently in operation to map the global distribution of soil moisture. However, at the longer L-band wavelength of these satellites, the emitting behavior of the land becomes very complex due to the unknown deeper penetration depth. This complexity leads to more uncertainty in calibration and validation of sate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 45 publications
7
51
0
Order By: Relevance
“…Journal of Advances in Modeling Earth Systems assumption of a constant Tb sensing depth in the L4_SM analysis likely causes bias in the L4_SM soil moisture estimates. Estimating the actual sensing depth and using this information in soil moisture assimilation systems are subjects of ongoing research (Lv et al, 2018(Lv et al, , 2019. Figure 2 further demonstrates that the Version 4 L4_SM estimates are better than estimates from the corresponding (model-only) Nature Run simulation, which again highlights the beneficial impact of the SMAP Tb data.…”
Section: 1029/2019ms001729mentioning
confidence: 94%
“…Journal of Advances in Modeling Earth Systems assumption of a constant Tb sensing depth in the L4_SM analysis likely causes bias in the L4_SM soil moisture estimates. Estimating the actual sensing depth and using this information in soil moisture assimilation systems are subjects of ongoing research (Lv et al, 2018(Lv et al, , 2019. Figure 2 further demonstrates that the Version 4 L4_SM estimates are better than estimates from the corresponding (model-only) Nature Run simulation, which again highlights the beneficial impact of the SMAP Tb data.…”
Section: 1029/2019ms001729mentioning
confidence: 94%
“…Air temperature was measured with a Platinum resistance thermometer, type HPM 45C, installed 1.5 m above the ground and precipitation (both rain and snow) was measured with a weight-based rain gauge, type T-200B. The depth profile of volumetric soil moisture content m v (m 3 m −3 ) was measured with an array of 20 capacitance sensors, type 5TM, that were installed at 135 depths ranging from 2.5 cm to 1 m (Lv et al, 2018). All sensors in the array are also equipped with a thermistor, enabling the measurement of the soil temperature depth profile T soil ( • C).…”
Section: Vegetationmentioning
confidence: 99%
“…A wide range of measurement techniques and protocols exist for setting up and performing ground-based observations for such evaluations. SMAP Cal/Val suggests that volumetric soil moisture should be observed in situ at 5 and 100 cm depth; optimal sensing and mounting depths are, however, still debated (Lv et al, 2016a(Lv et al, , 2018(Lv et al, , 2019. For core validation sites a minimum of six stations should cover one SMAP grid cell or footprint (O'Neill et al, 2015;Famiglietti et al, 2008); but this value has not yet been shown to guarantee the nominal accuracy by a thorough analysis (Jackson et al, 2012;.…”
Section: Introductionmentioning
confidence: 99%